Precise sound characteristics drive plasticity in the primary auditory cortex with VNS-sound pairing - Borland, Michael S.; Buell, Elizabeth P.; Riley, Jonathan R.; Carroll, Alan M.; Moreno, Nicole A.; Sharma, Pryanka; Grasse, Katelyn M.; Buell, John M.; Kilgard, Michael P.; Engineer, Crystal T. (Frontiers in Neuroscience, 2023)
Repeatedly pairing a tone with vagus nerve stimulation (VNS) alters frequency tuning across the auditory pathway. Pairing VNS with speech sounds selectively enhances the primary auditory cortex response to the paired sounds. It is not yet known how altering the speech sounds paired with VNS alters responses. In this study, we test the hypothesis that the sounds that are presented and paired with VNS will influence the neural plasticity observed following VNS-sound pairing. To explore the relationship between acoustic experience and neural plasticity, responses were recorded from primary auditory cortex (A1) after VNS was repeatedly paired with the speech sounds 'rad' and 'lad' or paired with only the speech sound 'rad' while 'lad' was an unpaired background sound. Pairing both sounds with VNS increased the response strength and neural discriminability of the paired sounds in the primary auditory cortex. Surprisingly, pairing only 'rad' with VNS did not alter A1 responses. These results suggest that the specific acoustic contrasts associated with VNS can powerfully shape neural activity in the auditory pathway. Methods to promote plasticity in the central auditory system represent a new therapeutic avenue to treat auditory processing disorders. Understanding how different sound contrasts and neural activity patterns shape plasticity could have important clinical implications.